Estudo do efeito de um gel neutralizador à base de catalase na liberação do oxigênio residual da estrutura dental após exposição ao peróxido de carbamida - Salomone, Paloma (2010)
The effects of the catalase-based gel in the release of residual oxygen in permanent human teeth submitted to 10% carbamide peroxide (Whitness perfect 10%) were assessed in vitro. The teeth were divided into specimens measuring 5X5X3 mm2 and randomly distributed into 3 groups: G1 negative control, nonbleached specimens; G2 positive control, only bleached specimens; and G3 bleached specimens and exposed to catalase-based experimental gel for 3 minutes. The bleaching treatment procedure was of 6 h a day for 14 days, and during the remaining hours the test specimens remained stored deionized water at 37oC. At the end of the bleaching treatment, G3 group was immersed in a receptacle containing 1 ml of catalase-based experimental gel for 3 minutes. The titrations were performed to determine the quantity of residual oxygen that each test specimen released, starting immediately after the end of the bleaching treatment and exposure or not to the gel containing catalase and repeated on the 1st, 2nd, 3rd, 4th, 5th, 10th and 15th day after the end of the bleaching treament. The nominal values of released residual oxygen were tabulated in spreadsheets and analyzed in the descriptive statistical program SPSS (Statistical Package for Social Sciences, version 18.0). Normality of distribution in each group was verified by the Shapiro-Wilk test and homoscedasticity among groups by the Levene test. The data were compared between the 3 groups at each experimental time by the Analysis of Variance and the Tukey s post hoc test (p<0.05). With the purpose of verifying within each group in which experimental period the release of residual oxygen was equal to the standard value found in G1, the paired t-test was used to compare each period. The values of release of residual O2 from G2 was equal to G1 after the 10th day after the end of the bleaching treatment, which occurred on the 5th day for G3. The results suggest that the use of the catalase-based experimental gel reduces by half the time required for complete release of residual oxygen from the tooth structure after bleaching.